Significance of surface-generated radicals in the gas-solid catalytic reactions - Syed Hassan, Syed Shatir Asghrar (Curtin University, 2010)
The conversion of light hydrocarbons with solid catalysts is an important class of reactions in the chemical and energy industries. Our knowledge on the exceedingly complex reaction kinetics of these catalytic reactions, especially the inter-influence between the reactions on catalyst and those in the gas phase, lags behind the requirement of technology development to improve efficiency and reduce emissions.The purpose of this study was to investigate the significance of surface-generated radicals in influencing the kinetics and mechanisms of gas-solid catalytic reactions. The results indicate that desorption is an important fate of the surface-generated radicals. The presence/absence of significant mass transfer resistance for radicals, which is different from that for the mass transfer of molecular species, determines the successful desorption/diffusion of radicals into the bulk gas phase.When a non-porous nickel mesh was used to catalyse the reactions between ethane and oxygen, it was found that the desorption/diffusion of radicals into the bulk gas phase could be facilitated by decreasing the mass transfer of radicals across the gas film around the nickel wires through increasing the gas flow rate traversing the mesh. The desorption of radicals increases the rate of chain reactions in the gas phase, resulting in the positive catalytic effects of nickel mesh. The nickel mesh can also have negative catalytic effects by quenching the gas-phase radicals by providing a surface to catalyse radical termination reactions.Many Ni-catalysed hydrocarbon oxidation reactions involve the reduction and oxidation (redox) of nickel catalyst itself. Results of this study show that the migration/diffusion of radicals on the surface, from the surface into the NiO bulk and from the surface into the gas phase can all have significant effects on the reduction kinetics. These in turn depend on the size of NiO crystallite, the presence/absence of rigid pore structure and the type of radicals formed on the catalyst surface.The use of fluidised nanoparticles as catalysts can lead to drastic reduction of reactor size for improved efficiency and reduced capital/operating costs. The catalytic oxidation of ethane with oxygen inside a fluidised bed of unsupported NiO nanoparticles in this study shows very different behaviour from the same reaction catalysed with silica-supported NiO catalysts. These differences can be explained by considering the difference in the resistance for the desorption of radicals into the bulk gas phase between the two catalytic systems.Overall, this study highlights the importance of considering the fates of surface-generated radicals in elucidating the kinetics and mechanism of gas-solid catalytic reactions. The original findings of this study are valuable for the development of innovative heterogeneous catalytic processes, especially the partial oxidation of light hydrocarbons, with high efficiency, low emission and low capital/operating costs.